Experimental study on failure mechanism of recycled coarse aggregate concrete under uniaxial compression. (1st January 2023) - Guo, Jia; Gao, Song; Liu, Ang; Wang, Hao; Guo, Xin; Xing, Fei; Zhang, Hengwu; Qin, Zhenwei; Ji, Yuan
Abstract: This paper investigated the micro-crack initiation, development, and interconnection process of recycled coarse aggregate concrete under uniaxial compressive loading from the mesoscale and macroscale. Furthermore, the strain change law of concrete cube in the failure process is recorded by Digital Image Correlation technology. The width and porosity of the interface transition zones were characterized by microhardness tests and backscattered electron imaging. The experimental results show that the compressive strength was increased by 15.77% and 29.68% by aggregate strengthening (RCA is immersed in nano-SiO2 solution) and mortar strengthening (silica fume was added during cement mixing), respectively, compared to untreated specimens. The microhardness of new mortar is increased, and the porosity of ITZOA-NM and ITZOM-NM is reduced by mortar strengthening. The probability of passing penetrating cracks decreases for strengthening interfaces. In the direction perpendicular to the compressive stress, the average strain values of the specimens are inversely proportional to their compressive strength. In the direction parallel to the compressive stress, the average strain fluctuation amplitude of the specimens is inversely proportional to their compressive strength. The strain variation of the specimens with mortar strengthening is the most moderate, and the strain fluctuation amplitude of the untreated specimens shows the most significant fluctuation. In addition, the probability of penetrating cracks passing strengthening interfaces was decreased. This work proposes an in-situ strain analysis method based on DIC technology that considers the inhomogeneity of concrete materials. The strengthening treatment will improve the micro and macro performance of recycled concrete, and correspond to the different performance of samples with different treatment methods in the macro failure process, establishing the relationship between the micro parameters and the macro performance. This provides a new way to study the failure process of recycled concrete from the micro and micro perspectives. Graphical abstract: Image 1 Highlights: Strain evolution of recycled concrete was investigated with considering the non-uniformity of materials. The in-situ test realized the visualization and quantitative analysis of the strain evolution process. Porosity of interface transition zone can be calculated from backscattered images. Targeted strengthening treatment will increase the strength of the corresponding interface transition zone.